Wassily Leontief's Research Program: Science, beliefs, institutions - Vincent Carret (Duke University, Center for the History of Political Economy (CHOPE), 2023)
Wassily Leontief met with decades of success for the development of input-output analysis, and yet he remained a staunch critic of the economics profession throughout his life. To understand his success, its limits, and the origins of his discontent, I separate the scientific activities of input-output from the system of belief built around it, and from the institutions set up to advance this research program. This leads to considering the interaction of Leontief's research program with other research programs through these three poles: the scientific debate, the collision of belief systems about the world, and an institutional fight for funds and researchers. The end result is a picture of how Leontief managed to build a successful research program where the science led to beliefs about the world that were able to justify building institutions promoting input-output, in an environment of competition and cooperation.
Keywords: B31; B41; L52; O21; P11; 330; Wassily Leontief; input-output; ideas; beliefs; institutions; competition; cooperation